Implementasi Profil Pelajar Berbasis Kearifan Lokal dalam Membangun Kesadaran Multikultural di Madrasah Tsanawiyah Singkawang - Qalam, M. Nuzurul; Hasan, Munawir; Rohman, Rizki Fathu (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This study explores the practices of the Project for Strengthening the Pancasila Student Profile (P5) and the Rahmatan lil 'Alamin Student Profile (PPRA), which are integrated with local wisdom. This study is a field study with a qualitative research approach. Data collection techniques were obtained through interviews with Islamic Religious Education teachers and students, direct observation, and documentation. This research shows the success of integrating P5 and PPRA with local culture. Three types of local culture are integrated: the typical spicy porridge food, the Tidayu dance, and wall magazines with the theme of tolerance. Its integration with P5 produces several values: morals towards fellow humans, knowing and appreciating culture, and collaboration. Meanwhile, its integration with PPRA produces values ​​of social piety, accommodating local culture and collaboration. Both mutually strengthen students' provisions in facing the differences that characterize a multicultural society.